Adenoid cystic carcinoma of the breast. An analysis of 21 cases (1969)
The clinical and pathologic findings in 21 patients with adenoid cystic carcinoma of the breast are presented. Nineteen of the 21 patients were living and well after treatment. Two patients died of unrelated causes. Local recurrence appeared in only 2 patients, 3 and 7 years following simple excision, but they were free of disease 9 and 14 years after subsequent mastectomy. No clinical or pathologic evidence of lymph node or distant metastasis was found in any of the patients. For these reasons, simple mastectomy is advocated as preferred treatment for adenoid cystic carcinoma, unless the tumor is particularly large or there are enlarged axillary lymph nodes. The favorable prognosis of patients with adenoid cystic carcinoma of the breast is in sharp contrast to that of patients with histologically identical tumors in other sites. Possible explanations for this striking difference in behavior are discussed. Copyright © 1969 American Cancer Society